Genomic deletion within GLDC is a major cause of non-ketotic hyperglycinaemia. Issue 3 (14th March 2007) - Kanno, Junko; Hutchin, Tim; Kamada, Fumiaki; Narisawa, Ayumi; Aoki, Yoko; Matsubara, Yoichi; Kure, Shigeo
Abstract : Background: Non-ketotic hyperglycinaemia (NKH) is an inborn error of metabolism characterised by accumulation of glycine in body fluids and various neurological symptoms. NKH is caused by deficiency of the glycine cleavage multienzyme system with three specific components encoded by GLDC, AMT and GCSH . Most patients are deficient of the enzymatic activity of glycine decarboxylase, which is encoded by GLDC . Our recent study has suggested that there are a considerable number of GLDC mutations which are not identified by the standard exon-sequencing method. Methods: A screening system for GLDC deletions by multiplex ligation-dependent probe amplification (MLPA) has been developed. Two distinct cohorts of patients with typical NKH were screened by this method: the first cohort consisted of 45 families with no identified AMT or GCSH mutations, and the second cohort was comprised of 20 patients from the UK who were not prescreened for AMT mutations. Results: GLDC deletions were identified in 16 of 90 alleles (18%) in the first cohort and in 9 of 40 alleles (22.5%) in the second cohort. 14 different types of deletions of various lengths were identified, including one allele where all 25 exons were missing. Flanking sequences of interstitial deletions in five patients were determined, and Alu -mediated recombination was identified in three of five patients. Conclusions: GLDC deletions are a significant cause of NKH, and the MLPA analysis is a valuable first-line screening for NKH genetic testing.